2007
DOI: 10.2215/cjn.01690407
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Target Hemoglobin Levels during the First Year of Epoetin Treatment in Patients with Chronic Kidney Disease

Abstract: Background and Objectives: Instability of hemoglobin levels during epoetin therapy is a new problem in hemodialysis. We evaluated extent and correlates of time in target, that is, the time spent with hemoglobin >11 g/dl during the first year of epoetin and its association with renal survival.Design, Setting, Participants, & Measurements: Data were collected in 917 visits for 12.0 mo in 119 patients with chronic kidney disease; thereafter, patients started renal survival analysis for 10.1 mo. At baseline, hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…Outcome variables during the baseline period were the measures of Hb variability, such as Hb fluctuations (18,19), residual standard deviation (SD) (20), within-patient SD for Hb (29), and time in target (21). We also calculated the area under the curve for Hb (Hb-AUC) to define the time-weighted average of Hb levels.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome variables during the baseline period were the measures of Hb variability, such as Hb fluctuations (18,19), residual standard deviation (SD) (20), within-patient SD for Hb (29), and time in target (21). We also calculated the area under the curve for Hb (Hb-AUC) to define the time-weighted average of Hb levels.…”
Section: Parametersmentioning
confidence: 99%
“…Indeed, on the one hand, omission of therapy with EPO is frequent throughout the whole spectrum of CKD (3)(4)(5)(6)(7)(8)(11)(12)(13)(14)(15)(16); on the other hand, several studies have reported that in treated patients, transitory reductions of Hb levels below target range are common and associated with worse outcome (17)(18)(19)(20)(21)(22). Specifically, in nondialysis patients with CKD, we found that intrapatient Hb variability occurred frequently, with most patients showing a limited extent of time spent with Hb at target (time in target), and that short time in target is associated with lower renal survival (21). Our previous study, however, left unanswered a critical question: Whether stability of Hb depends on individual responsiveness to EPO or intensity of therapeutic intervention.…”
mentioning
confidence: 99%
“…Interestingly, in one report, the risk of developing haemoglobin variability was greater with long-acting ESAs (Boudville et al, 2009). De Nicola and colleagues did not find any association between long-acting ESAs versus erythropoietin and haemoglobin variability (De Nicola et al, 2007). However, they observed that baseline haemoglobin level, first dose of ESA and initial iron supplementation were directly associated with the length of time-in-target haemoglobin.…”
Section: Esa Therapymentioning
confidence: 94%
“…al., 2008). In a study of 119 non-dialysis CKD patients, male gender was directly associated with increased time-intarget haemoglobin (De Nicola et al, 2007).…”
Section: Patient-level Factorsmentioning
confidence: 99%
See 1 more Smart Citation